ANALISIS KEKUATAN DINAR DAN DIRHAM SEBAGAI MATA UANG ANTI KRISIS - SURAHMAN SURAHMAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The theme of the article is based on economic principles Islam. The purpose of this research is to analyze the strength of the dinar and dirham as an anti-crisis currency. Research is the study of literature. In Islamic Economics which became the currency as a medium of exchange is the dinar and dirham. Money is a medium of exchange for the unit of measure of goods and labor. Since the implementation of a paper currency that is not no standardization of the value of gold and silver, led to the financial crisis. Dinar and Dirham has the power of being able to buy a wide range of commodities, thus making resistant to inflation. Dinar and dirham can be used by all countries in the world to be a medium of exchange, be it trade within the country and abroad.